Reverse triage: a systematic review of the literature - Pollaris, Gwen; De Bondt, Frieda; Sabbe, Marc (Frontiers in Disaster and Emergency Medicine, 2023)
Background: Many techniques to increase hospital surge capacity in case of a Mass Casualty Incident have already been studied but a new technique gained attention, Reverse Triage. The objective of this systematic review is to provide a comprehensive literature overview regarding the use of the Reverse Triage principle in Emergency and Disaster Medicine. Methods: A systematic literature review was carried out adhering to the PRISMA guidelines. Publications up to May 2023 of the databases Medline, Embase, CENTRAL, CINAHL and Web of Science were considered. Risk of Bias was assessed using the MINORS, ROBIS and JBI tool for observational, systematic reviews and expert opinions respectively. Results: The initial search identified 21259 unique records, of which 16 were included, consisting of two reviews, five expert opinions, and nine observational studies. Across studies, an overall surge capacity of 20-30% could be achieved by implementing reverse triage and even more when combined with other strategies. Furthermore, the American framework that comprehended a safe discharge protocol for inpatients, is being used in the development of new reverse triage discharge protocols. The risk of developing a complication (adverse event) due to early discharge is rather low. Discussion: Due to the heterogeneity of the included studies, interpretation of the results should be taken with caution. The most prominent differences were related to study size, university affiliation, healthcare system and patient characteristics. Nevertheless, implementing the reverse triage principle in MCI to guide early discharge of adult inpatients can create additional surge capacity with a minor occurrence of adverse events. A final assessment by a multidisciplinary discharge team (nurses and physicians) remains crucial.